Protocol for evaluating the effects of integrating music with taekwondo training in children with autism spectrum disorder: A randomized controlled trial - Clare C. W. Yu; Kam M. Mok; Emma Mak; Chun T. Au; Dorothy F. Y. Chan; Stanley Wu; Raymond C. K. Chung; Matthew C. K. Ip; Simpson W. L. Wong (PLoS ONE, 2025)
Background Children with autism spectrum disorder (ASD) are known to experience difficulties in coordinating fine- and gross-motor movement. Previous interventional studies have reported significant effect of exercise-based intervention programs on improving motor skills and alleviating symptoms in ASD; however, researchers are yet to know why some participants experienced less improvement than others. One plausible explanation for suboptimal treatment outcomes is insufficient engagement in the exercise programs due to the children’s difficulties in following instructions and performing the correct movements. In the proposed research, we will test the above speculation by manipulating the amount of music-therapy elements into a 10-week Taekwondo training program designed specifically for children with autism. Methods This is a randomized controlled trial. Seventy-two children aged 7 to 9 years who meet the diagnostic criteria of ASD will be recruited and randomized into either the “Taekwondo training with elements of music therapy” group or the “Taekwondo training alone” group. In both groups, the participating children will attend Taekwondo training sessions twice a week over 10 consecutive weeks. In the “Taekwondo training with elements of music therapy” group, elements of music therapy will be incorporated into the Taekwondo training. Assessment will be conducted before the program commences, immediately after the completion of the 10-week program, and 2 months after the post-test. The outcome domains to be evaluated include the immediate effects during the exercise sessions. These effects include the level of engagement in the exercise sessions (primary outcome), enjoyment, physical activity level, and rate of perceived exertion. Furthermore, the evaluation will also cover the overall effects of the training program on gross motor skills, Taekwondo skills performance, executive function, psychosocial functioning, and behavioral problems. Discussion/Findings The findings of this study will inform strategies for the promotion of physical activity and engagement among children with ASD when participating in exercise training classes. The study will also suggest the importance of regular physical activity for the physical and mental well-being of children with ASD. Trial registration Clinical trial registration: URL: http://www.clinicaltrials.gov. ClinicalTrials.gov Identifier: NCT06277778. Registered on 15 February 2024.